Structural, semantic, pragmatic and stylistic characteristics of coloronymes in yann martel’s novel “Life of Pi” - Vyshnytska, Y. S.; Вишницька, Яна Станіславівна (My University, 2021)
The article deals with analysis of coloronymes in Yann Martel's novel «Life of Pi». We investigate the coloronymes in literary texts that is why this novel is interesting for us because of the presence of coloronymes which we tried to classify into certain thematic groups and try to find the stylistic figures among them. Everybody knows that color is a very important category in life of humanity and every person. It has been studying from different sides and points of view, especially it is interesting to investigate them in literary texts of different writers. We can notice that authors very often use such coloronymes which are “popular” and usable in some period of time and according this we may understand which coloronymes are frequently used, which are occasional and which are rare. So we try to judge why some coloronyms use in this novel and what is their function in it.
Keywords: novel; coloronymes; literary text; pragmatic characteristic; stylistic characteristic; semantic and structural pecularities; thematic groups; stylistic figures